2022
DOI: 10.3389/fneur.2022.915357
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Pre-injury Migraines as a Vulnerability Factor for Worse Outcome Following Sport-Related Concussion

Abstract: BackgroundIndividuals with migraine disorders may be affected differently by concussions compared to individuals without migraine disorders. Prior studies on this topic have had mixed results. The purpose of this study was to systematically examine clinical outcomes following a sport-related concussion in athletes who have a pre-injury history of migraines.MethodsAll studies published prior to 15 May 2021 that examined pre-injury migraines as a possible predictor of clinical recovery from concussion were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Recovery times following concussion vary between athletes; the average time for clinical symptom resolution might be influenced by athlete sex, age, and the presence of pre-injury medical or psychological diagnoses. 1,4 Concussion modifiers are factors that might affect SRC recovery and influence a clinician's management, and include: [1][2][3]6,18,21,22 • a high number of concussive symptoms reported • reported severe acute and subacute symptoms • prolonged loss of consciousness (greater than one minute) at the time of the injury • a post-concussive seizure, following the injury • experiencing vestibular-ocular symptoms, such as dizziness and blurred vision • experiencing sleep disturbance in the 10 days after SRC • having a previous history of concussion • the age of the athlete (a more conservative approach is indicated in children)…”
Section: Recovery From Concussion Concussion-modifying Factorsmentioning
confidence: 99%
“…Recovery times following concussion vary between athletes; the average time for clinical symptom resolution might be influenced by athlete sex, age, and the presence of pre-injury medical or psychological diagnoses. 1,4 Concussion modifiers are factors that might affect SRC recovery and influence a clinician's management, and include: [1][2][3]6,18,21,22 • a high number of concussive symptoms reported • reported severe acute and subacute symptoms • prolonged loss of consciousness (greater than one minute) at the time of the injury • a post-concussive seizure, following the injury • experiencing vestibular-ocular symptoms, such as dizziness and blurred vision • experiencing sleep disturbance in the 10 days after SRC • having a previous history of concussion • the age of the athlete (a more conservative approach is indicated in children)…”
Section: Recovery From Concussion Concussion-modifying Factorsmentioning
confidence: 99%
“…Migraine is not just a headache; it is a severe neurological condition that could have a variety of negative repercussions on a man's life. Males with migraines are significantly less likely than females to utilize prescription medicines and significantly more likely to use only over-the-counter painkillers [36]. Migraine is a common chronic headache disorder that is characterized by recurrent attacks of moderate to severe pain.…”
Section: Migrainesand Menmentioning
confidence: 99%
“…The role of the pre-traumatic migraine (migraine prior to trauma) in SRC is poorly studied. A few studies have found significant relationships between pre-traumatic migraine and worse SRC consequences [ 10 ]. Zemek et al, conducted the largest cohort study of youths with acute concussion, aged 5− < 18 (N = 3063).…”
Section: Introductionmentioning
confidence: 99%